2001
DOI: 10.1074/jbc.m100562200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Antibodies Specific for the Pfs48/45 Protein of the Malaria Parasite Plasmodium falciparum

Abstract: We report the first construction of two combinatorial human phage display libraries derived from malariaimmune patients. Specific single-chain Fv fragments (scFv) against Pfs48/45, a gamete surface protein of the sexual stages of Plasmodium falciparum, were selected and analyzed extensively. The selected scFv reacted with the surface of extracellular sexual forms of the parasite and showed Pfs48/45 reactivity on immunoblot. The scFv inhibit binding of human malaria sera to native Pfs48/45 from gametocytes. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…Seven days after membrane feed, the number of infected mosquitoes and oocyst density were determined. Sera, mouse serum from M-Pfs10C-immunized group; Control, mean of five feeders with serum from control immunization; AM, arrhythmic mean oocyst number in 20 dissected mosquitoes; TN, total number of oocysts in 20 dissected mosquitoes; TBA, percentage of TB activity (19). cated (10C) residues 159 -428 were cloned into pMAL-p2x (New England Biolabs), resulting in N-terminal MBP fusions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven days after membrane feed, the number of infected mosquitoes and oocyst density were determined. Sera, mouse serum from M-Pfs10C-immunized group; Control, mean of five feeders with serum from control immunization; AM, arrhythmic mean oocyst number in 20 dissected mosquitoes; TN, total number of oocysts in 20 dissected mosquitoes; TBA, percentage of TB activity (19). cated (10C) residues 159 -428 were cloned into pMAL-p2x (New England Biolabs), resulting in N-terminal MBP fusions.…”
Section: Methodsmentioning
confidence: 99%
“…To detect epitopes of Pfs48/45, various mAbs of mouse origin, 32F5 (epitope I) and 32F1 (epitope IIb) (6,20), or rat origin, 85RF45.1 (epitope I), 85RF45.2b (epitope IIb), 85RF45.3 (epitope III), and 85RF45.5 (epitope V) (7,19), were used. HRP-conjugated anti-mouse IgG was purchased from Dako (P0161).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a phage display library from the peripheral blood of human patients, as reported previously. Roeffen et al (27) showed their biological activity and invasion inhibition using competitive ELISA with neutralizing antibodies. Lundquist et al (18) showed the neutralizing activity with an antibody-dependent cellular assay.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to make neutralizing antibody fragments against PvRII from an scFv library of naturally infected malaria patients. Some human recombinant antibodies against Plasmodium have been reported using the MSP protein of Plasmodium falciparum or the AMA protein of Plasmodium chabaudi as targets (13,18,27,30). We constructed a phage display library from the peripheral blood of human patients, as reported previously.…”
Section: Discussionmentioning
confidence: 99%